2005
DOI: 10.1080/01460860500227580
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behaviors Among School-age Children Associated With Perceptions of Stress

Abstract: Eating has been theorized to be useful as a coping strategy in response to stressful situations. However, investigation of this behavior in children is limited. The present study is a secondary cross-sectional analysis of longitudinal data that were collected from cohorts of fourth-, fifth-, and sixth-grader students. Perceived stress was correlated with unhealthy eating behaviors (r = .13, p < .001), as well as with the use of eating as a coping mechanism (r = .24, p < .001). Hispanic children reported using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 24 publications
0
41
0
1
Order By: Relevance
“…Nevertheless, this has seldom been studied in young children. To our knowledge, only one study in preadolescents demonstrated more snacking with more perceived stress (Jenkins et al, 2005) and one study showed more snacking in response to laboratory stressors (Roemmich, Wright, & Epstein, 2002). Our findings add to this knowledge on the relationship between stress and an unhealthier diet, thereby differentiating for more food indices and more stress variables.…”
Section: Stress and Dietary Patternsmentioning
confidence: 58%
See 2 more Smart Citations
“…Nevertheless, this has seldom been studied in young children. To our knowledge, only one study in preadolescents demonstrated more snacking with more perceived stress (Jenkins et al, 2005) and one study showed more snacking in response to laboratory stressors (Roemmich, Wright, & Epstein, 2002). Our findings add to this knowledge on the relationship between stress and an unhealthier diet, thereby differentiating for more food indices and more stress variables.…”
Section: Stress and Dietary Patternsmentioning
confidence: 58%
“…In those children between 8 and 13 years old, mutual correlations between stress, unhealthy food and eating as coping were detected, but mediation was not examined (Jenkins et al, 2005). Another study in 9 to 12 year old children found relations of emotional eating behaviour with both diet and stress, but reported no information on stress versus diet (Braet & Van Strien, 1997).…”
Section: Mediationmentioning
confidence: 97%
See 1 more Smart Citation
“…Research studies suggest that some adolescents may use food as a coping mechanism, showing a preference for high-energy, more palatable foods. [15][16][17][18] Mental distress could then be associated with higher intake of energy-dense foods that are low in nutritional value. Consequently, this type of change in eating behaviors could lead to increased caloric intake and excess weight.…”
Section: Introductionmentioning
confidence: 99%
“…Dans d'autres cas, ce stress peut se révéler difficile à gérer et devenir chronique par répétition. Il est alors susceptible d'impacter leur santé physiologique (Carter, Garber, Ciesla et Cole, 2006;Compas, Malcarne et Fondacaro, 1988) ou psychologique (Wagner, Compas et Howell, 1988) et de s'exprimer par des comportements variés, comme des manifestations anxieuses le plus souvent associées à la vie scolaire (Plancherel et al, 1997(Plancherel et al, , 2000, comme des troubles du sommeil, des maux de tête (Strine, Okoro, McGuire et Balluz, 2006;White et Farrell, 2005), des douleurs abdominales (Thomsen et al, 2002;White et Farrell, 2005), un absentéisme scolaire (Strine et al, 2006), une suralimentation (Jenkins, Rew et Sternglanz, 2005), de la fatigue, de la nervosité, de la tristesse, etc. Pourtant, les adultes ont généralement tendance à minimiser l'importance et l'impact de ces tracas quotidiens qui se répè-tent de façon insidieuse, alors que s'ils ne sont pas reconnus ni désamorcés à temps ils peuvent générer de véritables symptômes dépressifs.…”
Section: Introductionunclassified